2015
DOI: 10.1017/jfm.2015.320
|View full text |Cite
|
Sign up to set email alerts
|

Hairpin-like optimal perturbations in plane Poiseuille flow

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. In this work it is shown that hairpin vortex structures can be the outcome of a nonlinear optimal growth process, in a similar way as streaky structures can be the result of a linear optimal growth mechanism. With this purpose, nonlinear optimizations based on a Lagrange multiplier technique coupled with a direct-adjoint iterative procedure are performed in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 27 publications
11
35
0
Order By: Relevance
“…There is also further indirect evidence for this robustness to the choice T in that similar optimals are reported across a variety of flows: in plane Couette flow (Cherubini & De Palma 2013, 2014a; the Blasius boundary layer (Cherubini et al 2010(Cherubini et al , 2011(Cherubini et al , 2012; the asymptotic suction boundary layer (Cherubini et al 2015) and plane Poiseuille flow (Farano et al 2015(Farano et al , 2016). If T is too small, transients can obscure the situation (Rabin et al 2012) or new optimals become preferred (Pringle et al 2015, Farano 2015. Another potential problem is studying a flow where the turbulent state is not separated from the laminar-turbulent boundary or edge as far as the objective functional is concerned.…”
Section: Switching Basins Of Attraction: Minimal Seeds For Transitionmentioning
confidence: 63%
See 2 more Smart Citations
“…There is also further indirect evidence for this robustness to the choice T in that similar optimals are reported across a variety of flows: in plane Couette flow (Cherubini & De Palma 2013, 2014a; the Blasius boundary layer (Cherubini et al 2010(Cherubini et al , 2011(Cherubini et al , 2012; the asymptotic suction boundary layer (Cherubini et al 2015) and plane Poiseuille flow (Farano et al 2015(Farano et al , 2016). If T is too small, transients can obscure the situation (Rabin et al 2012) or new optimals become preferred (Pringle et al 2015, Farano 2015. Another potential problem is studying a flow where the turbulent state is not separated from the laminar-turbulent boundary or edge as far as the objective functional is concerned.…”
Section: Switching Basins Of Attraction: Minimal Seeds For Transitionmentioning
confidence: 63%
“…see Figure 22 of Cherubini et al 2011). Hairpin vortices are also found to be generated by optimals computed in plane Poiseuille flow using a very short T on the timescale of the Orr mechanism (Farano et al 2015).…”
Section: Switching Basins Of Attraction: Minimal Seeds For Transitionmentioning
confidence: 81%
See 1 more Smart Citation
“…These solutions are localized in the three spatial directions and do not present any symmetry. Whereas, for large values of E(0) and very small target times (T opt < 18), we obtain hairpin-like nonlinear optimal solutions (see also Farano et al (2015)), shown in the fourth subframe and represented by diamonds in the top frame of figure 2. The latter type of nonlinear optimal perturbation is associated with very large values of the initial energies, much larger than the transition threshold energy characterizing the other types of perturbations.…”
Section: Resultsmentioning
confidence: 92%
“…Further downstream, these vortices connect above interspersed high-speed streaks, forming lifted hairpins, which in turn break down, spawning spots. Quasi-streamwise vortices are not just natural features of streak instability; they have also been found to be the optimal, finite-amplitude perturbation that develops into hairpins in a short target time [14].…”
Section: Streamwise Vortices and Streaks In Boundary Layer Transitionmentioning
confidence: 99%